PEMANFAATAN WORDERSHARE QUIZ CREATOR DALAM PEMBUATAN SOAL-SOAL BAHASA ARAB - As'ari, Diah Rahmawati (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2017)
The development of technology and information give a positive impact on the development of education. Technology and information development provide various softwares to facilitate teachers in developing teaching media and creating attractive evaluation tool. An evaluation inArabic language teaching is to measure the extent to which students master the Arabic materials. Many softwares were developed to be evaluation tool in technology based learning, and of the one is Wordershare Quiz Creator. This software is quiz or test processing program that is easy to use. With this application, it is expected that Arabic language teachers are able to create technology-based Arabic language tests that can attract and improve students' enthusiast in doing the Arabic quiz.